Microstrip-fed Triangular UWB Microstrip Antenna Based on DGS - Abdurrahim Toktaş; Mehmet Yerlikaya; Enes Yiğit (International Journal of Applied Methods in Electronics and Computers, 2016)
An ultra-wideband (UWB) monopole microstrip antenna is designed in this study. The design consists of a radiating triangular patch antenna (TPA) fed through a 50 Ohm microstrip transmission line (MTL) constructed over a defected ground structure (DGS). The triangular monopole well is matched to MTL with inserting a thin strip line. The performance of the proposed antenna is numerically investigated using method of moments (MoM) and verified through measurements. Based on the measured results, the antenna operates over large frequency range of 2.6-18.2 GHz at -10 dB. This makes the design suitable for UWB applications.  The proposed antenna has better characteristics in terms of radiation pattern, peak gain and total efficiency across the operating ultra-wideband frequency range. Furthermore, the antenna system is suitable for near-millimetre wave applications, since the operating band reaches to 18.2 GHz.